The role of intraoperative monitoring in target selection in deep brain stimulation: A single centre study - Sandro Ibrulj; Dejan Georgiev; Žiga Samsa; Polona Mušič; Mitja Benedičič; Maja Trošt (Clinical Parkinsonism & Related Disorders)
Introduction: Intraoperative microelectrode recording (MER) and intraoperative test stimulation may provide vital information for optimal electrode placement and clinical outcome in movement disorders patients treated with deep brain stimulation (DBS). The aims of this retrospective study were to determine (i) how often the planned (imaging based) placements of electrodes were changed due to MER and intraoperative test stimulation in Parkinson’s disease (PD), dystonia and essential tremor (ET) patients; (ii) whether the frequency of repositioning changed over time; (iii) whether patients’ age or disease duration (in PD) influenced the frequency of repositioning. Methods: Data on the planned and the final placement of 141 electrodes in 72 consecutive DBS treated patients (52 PD, 11 dystonia, 9 ET) was collected over the first 8 years of DBS implementation in a single center. An association between the rate of electrode repositioning and the patients’ age, disease duration and the time/year of implementation was explored. Results: Analysis of all targets showed a change in final electrode placement in 39.7 % (56/141); 39.8 % (41/103) in PD, 40.9 % (9/22) in dystonia and 37.5 % (6/16) in ET. Annual analysis showed a decrease in rate of repositioning between the centre’s first and eighth year (p = 0.013) of implementation. No correlation was found between electrode repositioning rate and patient age (p = 0.42) nor disease duration (p = 0.09) in PD. Conclusion: This retrospective analysis confirms the benefit of MER and intraoperative test stimulation during DBS surgery in determining the final electrode position during the early / initial period of implementing the procedure. Our findings show a learning curve in successful preoperative planning in our centre achieved through experience.